Exceptional band touching for strongly correlated systems in equilibrium. (24th July 2020) - Yoshida, Tsuneya; Peters, Robert; Kawakami, Norio; Hatsugai, Yasuhiro
Abstract: Quasi-particles described by Green's functions of equilibrium systems exhibit non-Hermitian topological phenomena because of their finite lifetime. This non-Hermitian perspective on equilibrium systems provides new insights into correlated systems and attracts much interest because of its potential to solve open questions in correlated compounds. We provide a concise review of the non-Hermitian topological band structures for quantum many-body systems in equilibrium, as well as their classification.